Perancangan Sistem Agenda Kegiatan Dokumentasi Pimpinan pada Bagian Protokol dan Komunikasi Pimpinan Pemerintahan Kabupaten Situbondo Berbasis Website (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The rapid development of information technology has encouraged government institutions to transform the way they manage data and deliver public services. The Protocol and Leadership Communication Division (Prokopim) of Situbondo Regency plays a strategic role in managing the schedules of regional leaders and documenting each official activity as a form of accountability. Currently, these processes are still managed manually, which causes obstacles in recording, searching, and reporting data. Such limitations reduce efficiency and transparency, indicating the urgency of a structured, accessible, and integrated web-based information system. This research aims to design a web-based system that integrates employee data, leadership agendas, and documentation records into a single platform. The research method combines field observations, interviews with Prokopim staff, and literature studies to analyze user requirements. The system design adopts the Waterfall model, which includes requirement analysis, database design, user interface design, and system modeling using Unified Modeling Language (UML) diagrams such as use case, activity, and sequence diagrams. Database structures are represented through class diagrams, while user interface designs are developed using prototyping. The findings of this study produce a system blueprint that provides a structured framework for digitalizing agenda and documentation processes. The proposed design improves accessibility, accuracy, and efficiency in managing leadership activities. Furthermore, this system can be considered as a practical model for applying digital transformation in government institutions, supporting better accountability and service quality in the public sector.